Pendekatan Pembelajaran Humanistik dan Retensi Matematis Siswa: Peran Kemampuan Awal Matematis dan Level Sekolah - Suhandri Suhandri; Saifullah Rahman; Annisa Rahmadani (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2026)
This study aims to analyze the effect of a humanistic learning approach on students' mathematical retention abilities and examine differences based on school level. The study used a quasi-experimental method with a non-equivalent control group design. The study sample consisted of 120 eighth-grade junior high school students in Riau Province from medium and low-level schools. The experimental group received learning with a humanistic approach, while the control group received direct learning. Initial mathematical ability (KAM) was assessed through a pretest to ensure group equality, while mathematical retention ability was evaluated through a test administered three months after the learning was completed. Data were analyzed using descriptive statistics and the Mann–Whitney test. The results showed that the increase in mathematical retention ability of students who received a humanistic approach was higher than that of students who received direct learning, with an average N-gain of 0.77 and 0.72, respectively. The Mann–Whitney test results showed that the difference was significant (p = 0.003). Based on school level, the humanistic approach resulted in significantly better retention in medium-level schools (p = 0.024), but did not show a significant difference in low-level schools (p = 0.185). These findings indicate that the humanistic approach is effective in improving students' mathematics retention, especially in schools with higher levels of academic readiness.